Asthma patients' and physicians' perspectives on the burden and management of asthma. (September 2021) - Chapman, Kenneth R.; An, Li; Bosnic-Anticevich, Sinthia; Campomanes, Celeste M.; Espinosa, Jerónimo; Jain, Priya; Lavoie, Kim L.; Li, Jing; Butta, Aman K.
Abstract: Background: The 2021 Global Initiative for Asthma (GINA) report recommends as-needed inhaled corticosteroid (ICS)/formoterol irrespective of severity, and maintenance and reliever treatment (MART) from GINA Step 3 as part of Treatment Track 1, partly based on the SYGMA studies. We investigated how current clinical practice in Australia, Canada, China and the Philippines relates to latest GINA recommendations. Methods: Patients and physicians were recruited from online panels between July and August 2020 and invited to complete an online survey. Inclusion criteria: age ≥18 years, current/past physician diagnosis of asthma (patients); primary care (Canada also included respirologists/respiratory therapists), treating ≥4 patients with asthma per month, ≥3 years in clinical practice (physicians). Results: Overall, 1216/70, 183 patients and 803/8376 physicians replied and were eligible for inclusion. Only 8–15% of patients were using MART; 66–81% used regular maintenance therapy with/without an as-needed reliever. Across the four countries, physicians classified 48–63% of their patients as mild (GINA Steps 1– 2 ) and 28–36% as moderate (GINA Steps 3–4). Generally, physicians rated symptom control over exacerbation reduction as their main treatment goal; patients also ranked symptom relief as very important. Approximately 9–29% of patients and 24–45% of physicians were unaware of MART, and among those who prescribed MART, 80–95% prescribed an additional (non-ICS) as-needed reliever. Interpretation: Most physicians prioritized managing asthma symptoms over exacerbations. A lack of awareness and understanding of MART dosing exists among physicians. Practical strategies are required to implement GINA recommendations effectively in real-world clinical practice and to identify appropriate patients for MART. Highlights: Most physicians prioritize symptom control over reducing exacerbations. Patients also consider symptom relief to be very important. Physicians classified a substantial proportion of patients as GINA Step 3 or higher. A large number of physicians and patients were not aware of MART. Most physicians had prescribed an additional as-needed reliver alongside MART.